Titan Krios–Class Cryo-EM as Research Infrastructure: Workflows, Automation, and Shared-Access Models - David Aphkhazava; Levan Gulua; Cezar Goletiani; Nino Nebieridze; Nino Maziashvili; Nodar Sulashvili; Mzia Tsiklauri; Archil Chirakadze; Manana Makharadze; Lolita Shengelia; Tamar Okropiridze (Research Reviews, 2026)
Titan Krios–class 300 kV cryogenic transmission electron microscopes (cryo-TEMs) have fundamentally shifted cryo-EM from an expert-driven, low-resolution specialty into a shared, facility-grade research platform that routinely supports near-atomic to atomic structure determination, and increasingly, in situ cellular structural biology via cryo-electron tomography (cryo-ET). This transformation is best framed as an infrastructure story: hardware evolution (direct electron detectors, energy filtering, stable 300 kV optics, the next-generation Krios 5 platform launched in April 2025), software maturation (motion correction, Bayesian reconstruction, deep-learning particle pickers, and now fully integrated AI end-to-end pipelines), and operational models (remote-access automation, national service centers, shared pharmaceutical facilities). The Electron Microscopy Data Bank (EMDB) surpassed 50,000 cumulative depositions in 2025 and recorded more than 10,000 new releases in a single calendar year for the first time—a quantitative marker of the technique's maturity and scale [1, 2]. The global cryo-EM structure analysis services market was valued at USD 1.30 billion in 2025 and is projected to reach USD 2.51 billion by 2032 [3]. Specimen preparation—vitrification—remains the primary rate-limiting step even as downstream imaging and computing reach near-factory throughputs, and it is now the focus of intense automation efforts including novel droplet-based and MEMS nanofluidic approaches [4, 5]. The most significant recent software development is the emergence of fully integrated AI platforms—exemplified by the SMART platform (2025)—that chain automated data collection, 3D reconstruction, and atomic model building into a single, web-accessible workflow [6]. These trends collectively point toward a near-future of 'push-button' cryo-EM that is accessible to researchers with minimal specialist training.